2006
DOI: 10.1002/cbic.200600155
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of an Intercalator–Polyamide Hairpin Designed to Target the Inverted CCAAT Box 2 in the Topoisomerase IIα Promoter

Abstract: The synthesis and DNA-binding properties of a novel naphthalimide-polyamide hairpin (3) designed to target the inverted CCAAT box 2 (ICB2) site on the topoisomerase IIalpha (topoIIalpha) promoter are described. The polyamide component of 3 was derived from the minor-groove binder, 2, and tailored to bind to the 5'-TTGGT sequence found in and flanking ICB2. The propensity of mitonafide 4 to intercalate between G-C base pairs was exploited by the incorporation of a naphthalimide moiety at the N terminus of 2. Hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Another example is that of Lee et al 88 who combined the intercalation effect of the 1, Another example of the use of chromophores conjugated to peptidyl chains with the view of achieving sequence selective recognition of DNA is that of by Iverson et al 89 who developed the peptide 73 (and many other related structures) as a DNA bis-intercalator. While the scope of this review is not to explore the field of these related naphthalimide structures, we end this review on this particular naphthalene diimide example, giving its close relation to the topic herein.…”
Section: Bmentioning
confidence: 99%
“…Another example is that of Lee et al 88 who combined the intercalation effect of the 1, Another example of the use of chromophores conjugated to peptidyl chains with the view of achieving sequence selective recognition of DNA is that of by Iverson et al 89 who developed the peptide 73 (and many other related structures) as a DNA bis-intercalator. While the scope of this review is not to explore the field of these related naphthalimide structures, we end this review on this particular naphthalene diimide example, giving its close relation to the topic herein.…”
Section: Bmentioning
confidence: 99%
“…In view of these interesting results, Braña et al in 1995 synthesized a series of 5-amino-8-nitronaphthalimides to combine the electron withdrawing effects of the nitro group and the electron donating aspects of the amino group [6]. These compounds (59)(60)(61)(62)(63)(64)(65) were tested for their in vitro cytotoxicity against human CX-1 colon and LX-1 lung carcinomas ( Table 3) and showed higher activity than amonafide and mitonafide [3]. Two of them also showed promising in vivo activity in the L1210 leukemia and Fig.…”
Section: Monomeric Naphthalimides: Design Synthesis Cytotoxic Activmentioning
confidence: 99%
“…Bailly et al [61] reported observations which strengthened the case for elinafide binding via the major groove of the double helix, in contrast to nearly all common intercalating drugs, which could be important in explaining the unique biological selectivity of bis-naphthalimides. Flores et al [62] have reported the synthesis of a novel naphthalimide-polyamide hairpin, designed to target the inverted CCAAT box 2 (ICB2) site on the topo II promoter. The compound appears to selectively bind to the ICB2 site by simultaneous intercalation and minor-groove binding.…”
Section: A) Topoisomerase II Inhibitionmentioning
confidence: 99%
“…The synthesis and anticancer activities of a numerous compounds that intercalate into DNA have been reported recently [7][8][9][10][11][12][13]. Some b-carboline alkaloids such as harmine and its derivatives, are highly cytotoxic against human tumor cell lines [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%